Automatic vehicle detection in infrared imagery using a fuzzy inference-based classification system. - Nelson, B.N (IEEE Transactions on fuzzy systems)
This paper describes a unique approach of using a fuzzy inference system for target detection and classification. It first describes the methods that are used to identify regions of interest within each frame of the infrared imagery. Next, the specific data features that are extracted from these regions of interest are described. The fuzzy inference system used in this application is described. This description includes discussions of the feature input and system output membership functions, the rules used in the inference system, and the logical operations, implication, aggregation and defuzzification methods employed. Finally, results attained by applying the described approach to a ?blind? closing sequence data set are provided and conclusions are drawn. The developed techniques have proved to be robust and have demonstrated an ability to properly classify a variety of targets in different clutter environments. The described approach can easily be expanded to utilize other feature inputs